1998
DOI: 10.1136/gut.42.4.511
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a novel prokinetic drug, R093877, on gastrointestinal transit in healthy volunteers

Abstract: Background-Stronger prokinetic agents which specifically enhance transit in different parts of the gut are required. R093877 is a novel 5-HT 4 agonist prokinetic compound which is chemically related to cisapride but believed to have greater eVect on colonic activity. Aims-To evaluate the eVects of R093877 on bowel function, upper and lower gut transit, visceral sensitivity, and sphincter function in healthy volunteers in a double blind, placebo controlled, crossover study. Methods-The study consisted of five c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
76
1
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 16 publications
11
76
1
3
Order By: Relevance
“…Prucalopride has high selectivity and affinity to 5-HT 4 receptors, which enhance enterokinetic properties in the gastrointestinal tract without risk of cardiovascular toxicity [Emmanuel et al 1998]. Prucalopride primarily acts by releasing 5-hydroxytryptamine (5-HT), which secondarily releases Acetylcholine (Ach) and calcitonin generelated peptide from the intrinsic primary afferent neurons [De Maeyer et al 2008].…”
Section: Prucalopridementioning
confidence: 99%
“…Prucalopride has high selectivity and affinity to 5-HT 4 receptors, which enhance enterokinetic properties in the gastrointestinal tract without risk of cardiovascular toxicity [Emmanuel et al 1998]. Prucalopride primarily acts by releasing 5-hydroxytryptamine (5-HT), which secondarily releases Acetylcholine (Ach) and calcitonin generelated peptide from the intrinsic primary afferent neurons [De Maeyer et al 2008].…”
Section: Prucalopridementioning
confidence: 99%
“…Per entrambi questi end point secondari le differenze tra prucalopride minuisce la consistenza delle feci. Le dosi studiate sono risultate pressoché equi-efficaci nell'accelerare il transito colico [43][44][45][46][47][48]. Nei volontari sani prucalopride riduce il tempo di transito nei segmenti destro e sinistro del colon, senza modificare il transito nel sigma retto e le funzioni anorettali [46,47].…”
Section: Trattamenti Farmacologiciunclassified
“…Le dosi studiate sono risultate pressoché equi-efficaci nell'accelerare il transito colico [43][44][45][46][47][48]. Nei volontari sani prucalopride riduce il tempo di transito nei segmenti destro e sinistro del colon, senza modificare il transito nel sigma retto e le funzioni anorettali [46,47]. Si ritiene che l'effetto di accelerazione del transito sia dovuto alla stimolazione delle contrazioni propagate di grande ampiezza (HAPACs) e all'aumento delle contrazioni segmentali non propagate [48].…”
Section: Trattamenti Farmacologiciunclassified
See 1 more Smart Citation
“…Among patients with constipation, however, the very same authors using the exact same scintigraphic technique found that prucalopride in doses of 2 or 4 mg daily accelerated whole gut, gastric, small bowel and colonic transit in constipated patients [Bouras et al 2001]. Importantly, prucalopride did not appear to adversely affect a number of parameters of anorectal motor function or impair rectal sensation in either healthy volunteers or patients with constipation [Sloots et al 2002;Bouras et al 2001;Poen et al 1999;Emmanuel et al 1998]. In studies of colonic motility, prucalopride has been shown to be stimulatory [De Schryer et al 2002;Emmanule et al 2002].…”
Section: Ibs-u (Unclassified)mentioning
confidence: 99%